The Concept of Inclusive Education in the Islamic Perspective - Yusron, Moh Alwi; Rochmat, Cecep Sobar; Dewi , Mutiara (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2024)
Inclusive education is an educational approach aimed at providing equitable access to all individuals regardless of differences in background, abilities, or specific conditions. In Islam, the concept of inclusivity is deeply rooted in values of justice, compassion, respect for diversity, and social responsibility. This study aims to explore the concept of inclusive education in Islam by examining its foundational values, philosophical underpinnings, and applications in the modern context. This research employs a library research methodology, analyzing primary sources such as the Qur’an, Hadith, and classical and contemporary Islamic scholarly works, as well as secondary sources from recent academic literature. Data are analyzed qualitatively using a descriptive-analytical approach to identify the principles of inclusive education in Islam. The findings indicate that Islam comprehensively supports inclusive education through universal values that are adaptable to changing times. Principles such as social justice, compassion (rahmah), and respect for diversity position Islam as a faith that promotes inclusivity. This study also compares Islamic perspectives with modern educational theories, highlighting the relevance of Islamic values in addressing the challenges of inclusive education in the globalized era. The implications of this study include the necessity of integrating Islamic values into modern education systems to create more equitable and harmonious learning environments. However, the study's limitation lies in the lack of empirical examination to assess the effectiveness of applying these values in practical educational settings. This research contributes original insights by providing philosophical and practical perspectives from Islam to support inclusive education, thereby enriching the global discourse on education for all.